Irrational beliefs and social and psychological adaptation in adults with chronic pain - Gur, Oleg A.; Klyshevich, Natalya Yu. (Journal of the Belarusian State University. Philosophy and Psychology, 2026)
Adults with chronic pain were found to have pronounced irrational should beliefs about themselves and others, as well as higher levels of irrational thinking in general. These differences were found to be statistically significant. A significant number of correlations were found between the variables studied: the higher the irrationality of thinking, the lower the respondents’ socio-psychological adaptation. In the group of adults with chronic pain, the highest number of correlations were found between the «catastrophising», «should beliefs about others», and «low frustration tolerance» scales and social and psychological adaptation indicators.